LITERARY TRANSLATION AND ITS PROBLEMS - Usarova Muxlisaxon; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Abstract; Literary translation plays a vital role in ensuring intercultural understanding, the exchange of artistic values, and the global circulation of literary heritage. As literature embodies not only linguistic structures but also a nation’s cultural memory, worldview, emotional depth, and aesthetic principles, translating literary works from one language into another presents unique complexities. This research explores the fundamental nature of literary translation, emphasizing its creative dimension and the translator’s responsibility as both an interpreter and a co- creator of meaning. The study examines the major linguistic, stylistic, cultural, and poetic challenges faced by translators. These include the difficulty of rendering author-specific styles, idiomatic expressions, metaphors, wordplay, cultural realia, dialectal features, and character-specific speech patterns. Particular attention is given to the issue of preserving national color and connotative meaning, which often resist direct translation and require culturally sensitive strategies such as adaptation, functional equivalence, or explanatory translation.